The effect of physical therapy in the treatment of patients with cervical dystonia with or without concomitant use of botulinum toxin - Stanković, Ivona; Čolović, Hristina; Živković, Vesna; Stamenović, Jelena; Stanković, Anita; Zlatanović, Dragan; Živković, Danijela; Stanković, Tamara (Vojnosanitetski pregled, 2020)
Background/Aim. Botulinum toxin is a basic, recommended method of treatment in controlling cervical dystonia (CD). Physical therapy has limited effect due to the nature of the disease that is a result of a disorder in structures and relationships of the basal ganglia. The aim of this study was to analyze the effect of physical therapy applied as monotherapy, or with parallel application of botulinum toxin in patients with CD. Methods. Randomized controlled clinical pilot study included 14 patients diagnosed with idiopathic CD. All patients were initially assessed by using the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) and Torticollis Rating Scale (Tsui scale). In the control group, composed of 5 patients, the treatment included only physical therapy. The experimental group (9 patients) was first given botulinum toxin, and physical therapy was applied after five days. Physical therapy was conducted five times a week in the period of two weeks at the Clinic. Patients of both groups were instructed to continue with the physical therapy at home. The effects of treatment were analyzed after 1, 3 and 6 months using TWSTRS and Tsui scale. Results. At the beginning of the investigation, the differences in TWSTRS and Tsui scale between the groups were not significant. In the control group, after 1 month, significant improvement was achieved in all three parts of the TWSTRS. After 3 and 6 months, the effects of physical therapy were reduced to control levels. In the experimental group, highly significant increase of all parameters of TWSTRS was noted after 1, 3 and 6 months. In the control group, highly significant decrease of changes in Tsui scale was noticed only after one month while in the experimental group, it was maintained after 3 and 6 months. Conclusion. Application of physical therapy provides a significant improvement in disease severity, but the effect is better and of longer duration when combined with the botulinum toxin.